The impact of chest radiography on the diagnosis, clinical management and outcome of acute lower respiratory infections in children - Swingler, George Henry (Department of Public Health and Family Medicine, 2023)
Background. When available, chest radiography is widely used in acute lower respiratory infections in children. Its impact on clinical outcome is unknown. Methods. A randomised controlled trial was performed of 522 children aged 2 to 59 months who met the World Health Organisation case definition for pneumonia. The main outcome was time to recovery, measured in a subset of 398 participants who offered a telephone number. Subsidiary outcomes included diagnosis, elements of clinical management and subsequent use of health facilities. Findings. There was a marginal improvement in time to recovery, which was not clinically significant. The median time to recovery was seven days in both groups, 95% CI 6-8 days and 6-9 days in the radiograph and control groups respectively (p=0.50, log rank test). The hazard ratio for recovery was 1.08 (95% CI 0.85 to 1.34). This lack of effect was not modified by clinicians' experience and no sub-groups of children were identified in whom the radiograph had an effect. Pneumonia was diagnosed more often in the radiograph group (14.4% vs. 8.8%, p=0.03) and bronchiolitis less often ( 44% vs. 56%, p=0.005). Antibiotic usage was higher in the radiograph group (60.8% vs. 52.2%, p=0,05). There were no differences in subsequent health facility usage. Interpretation. Despite a net change in diagnosis and an increase in antibiotic usage, chest radiography did not affect clinical outcome in outpatient children with acute lower respiratory infection. This lack of effect was independent of clinicians' experience. There were no clinically identifiable sub-groups of children within the World Health Organisation case definition of pneumonia who benefited from radiography. It is concluded that routine use of chest radiography is not beneficial in ambulatory children over two months of age with acute lower respiratory infection.